(untitled) (Baghdad Science Journal, 2016)
The present study includs the isolation and identification of Keratinophilic fungi in fresh water samples collected from Tigris river in Baghdad, Iraq. Samples were collected from different districts of Baghdad (Al-Rustumia, Madina Al-Teb, Al-Azamia, Al-Kadimia, Al-Dorha and Al-Kanah). The water samples were examined for keratinophilic fungi by the plating method culturing and Hair Baiting Technique. A total number of 18 genera are recorded, in which the Tigris water indicates an impressive diversity of fungi. A variety of fungal strains were isolated from river water, out of 814 fungal colonies, Aspergillus terrus (5.5%) was the most frequent species, followed by Aspergillus niger (5.2%) then Rhizopus stolonifer (3.3%). The results revealed that the highest number of fungal species are found in water surface near the margin (75%) followed by the fungi isolated from water surface in the middle of the river (25%), whereas the number of fungi in 50 cm depth from water surface near the margin and 50 cm depth from water surface in the middle of the river is 17.10% and 12.20% species respectively. The results suggest that the Tigris river is a potential transmission route of fungi and a healthily hazard mainly for the immune depressed individual.